2023
DOI: 10.3390/su15054620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Teachers’ Commitment to the Relationship between Transformational Leadership and Sustainable Teaching Performance

Abstract: In the field of education, ongoing processes, and optimal schoolwork outcomes require educational leadership, especially in developing countries, due to the lack of sustainable teaching performance and effective leadership. The present study aims to examine the mediating role of teachers’ commitment to transformational leadership and sustainable teaching performance. The sample of the study was selected using a stratified random sampling technique. Out of the 450 copies distributed to the participants, only 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Studies have found that principal transformational leadership is positively related to teachers’ teaching behaviours and work performance [ 16 , 33 , 34 ]. PTL can pose significant influences on teachers’ teaching practice through such leadership behaviours as defining inspirational goals and persuasive values for teaching excellence, stimulating teachers’ competences that foster innovation, and creating empowering and facilitative structures that spur teaching change [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have found that principal transformational leadership is positively related to teachers’ teaching behaviours and work performance [ 16 , 33 , 34 ]. PTL can pose significant influences on teachers’ teaching practice through such leadership behaviours as defining inspirational goals and persuasive values for teaching excellence, stimulating teachers’ competences that foster innovation, and creating empowering and facilitative structures that spur teaching change [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…simply because a good leader is capable of smoothly and effectively leading a team (Alzoraiki, et al, 2023). Media organizations have the power to shape public opinion and influence policy decisions, and innovative media leaders are able to use this power to…”
Section: Role Of Innovative Media Leadership In Driving Sustainable D...mentioning
confidence: 99%
“…We have identified four innovation characteristics and four contextual variables (technology competence, company size, competitive demand, and partner readiness) as determinants of post-adoption use, and we postulate that usage serves as an intermediate link to influence firm efficiency. Since variables in the TOE setting can vary across different contexts, additional variables may need to be added for enrichment [57,58]. To facilitate model validation via subsequent statistical analysis, a priori assumptions based on a positive, deterministic philosophical framework were developed.…”
Section: Technology-organization-environment (Toe)mentioning
confidence: 99%